SKOL : Livret de programmation 1994-1995. - Beaudoin, Marie-France; Beaudoin, Stéphanie; Bergeron, Charles; Blanchard, Francis; Brouillette, Marc-André; Bérubé, Anne; Cotton, Sylvie; Dion, François; Fortier, Louis; Lefebvre, Véronique; Roy, Daniel; Théorêt, Yves; et al. (Montréal : Centre des Arts Actuels SKOL, 1995)
Baillargeon, Christiane ; Boisseau, Lise ; Chabot, Joceline ; Côté, Mario ; Dubois, Geneviève ; Fortier, Louis ; Morier, Pauline ; Quintas, Eva ; Robitaille, Pierre ; Roy, Daniel ; Sainte-Marie, Sylvie ; Tremblay, Jocelyne ; Robert, Lucie ; Trahan, Carl ; Cormier, François ; Paré, Claude ; Poupart, Gisèle ; Shukla, Tara ; Lorrain, Michèle ; Ashton, Anne ; Lavaillante, Renée ; Lalonde, Francine ; Lord, Hélène ; Danylchuk, Jacki ; LeTourneux, François ; Gauthier, Jean-Pierre ; Ouellet, Marie ; Bergeron, Gin
biografie
Frans
boek